Impact of Age on Human Adipose Stem Cells for Bone Tissue Engineering - Dufrane, Denis (Cell Transplant, 2017)
Bone nonunion is a pathological condition in which all bone healing processes have stopped, resulting in abnormal mobility between 2 bone segments. The incidence of bone-related injuries will increase in an aging population, leading to such injuries reaching epidemic proportions. Tissue engineering and cell therapy using mesenchymal stem cells (MSCs) have raised the possibility of implanting living tissue for bone reconstruction. Bone marrow was first proposed as the source of stem cells for bone regeneration. However, as the quantity of MSCs in the bone marrow decreases, the capacity of osteogenic differentiation of bone marrow stem cells is also impaired by the donor’s age in terms of reduced MSC replicative capacity; an increased number of apoptotic cells; formation of colonies positive for alkaline phosphatase; and decreases in the availability, growth potential, and temporal mobilization of MSCs for bone formation in case of fracture. Adipose-derived stem cells (ASCs) demonstrate several advantages over those from bone marrow, including a less invasive harvesting procedure, a higher number of stem cell progenitors from an equivalent amount of tissue harvested, increased proliferation and differentiation capacities, and better angiogenic and osteogenic properties in vivo. Subcutaneous native adipose tissue was not affected by the donor’s age in terms of cellular senescence and yield of ASC isolation. In addition, a constant mRNA level of osteocalcin and alkaline phosphatase with a similar level of matrix mineralization of ASCs remained unaffected by donor age after osteogenic differentiation. The secretome of ASCs was also unaffected by age when aiming to promote angiogenesis by vascular endothelial growth factor (VEGF) release in hypoxic conditions. Therefore, the use of adipose cells for bone tissue engineering is not limited by the donor’s age from the isolation of stem cells up to the manufacturing of a complex osteogenic graft.